2020
DOI: 10.29344/0717621x.42.2600
|View full text |Cite
|
Sign up to set email alerts
|

La lectura y el futuro profesor: una aproximación a sus creencias acerca de la lectura

Abstract: Con el objetivo de indagar en las creencias de futuros docentes acerca de la lectura, se realizó un análisis de contenido textual de tipo mixto. Participaron 364 docentes en formación de Educación Básica (n = 202) y Educación Parvularia (n = 162) provenientes de nueve universidades chilenas. Los discursos de estos futuros docentes dan cuenta de creencias diversas referentes a la lectura (inter e intrasujetos) que van desde la herramienta hasta la práctica cultural. Contra lo esperado, se constata empíricamente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…These results are aligned with various studies that have highlighted the close relationship between reading and writing. Reading can be understood as a complex and interactive mental process that requires psycholinguistic skills to decode and understand (González Ramírez et al, 2020). It can be assumed that the reader is the one who constructs the meaning and interprets it based on his or her prior knowledge schemes and the new information presented in the text (Estaba & López, 2022;Noriega Vidal, 2018;Hurtado et al, 2018;Patricia, 2022;Sánchez Cruz et al, 2022).…”
Section: Source: Teachersmentioning
confidence: 99%
“…These results are aligned with various studies that have highlighted the close relationship between reading and writing. Reading can be understood as a complex and interactive mental process that requires psycholinguistic skills to decode and understand (González Ramírez et al, 2020). It can be assumed that the reader is the one who constructs the meaning and interprets it based on his or her prior knowledge schemes and the new information presented in the text (Estaba & López, 2022;Noriega Vidal, 2018;Hurtado et al, 2018;Patricia, 2022;Sánchez Cruz et al, 2022).…”
Section: Source: Teachersmentioning
confidence: 99%
“…Regarding the beliefs of preservice teachers, about reading, it is pertinent to mention the study by González Ramírez et al (2020) , where it was reported that a group of prospective primary and early childhood education teachers primarily recognize three facets of reading: functional, cognitive, and social. The results demonstrate that future teachers define reading based on its functional facet (71%), followed by the cognitive facet (25%), and lastly, the social facet (4%).…”
Section: Introductionmentioning
confidence: 99%
“…Otras investigaciones relevantes para esta contribución las constituyen aquellas basadas en las creencias del profesorado sobre la lectura. En esa línea podemos aludir a Díaz Armas (2008), González Ramírez et al (2020, o Munita (2016Munita ( y 2018. Pese a que las tendencias sociales y educativas de la última década vienen marcadas por la modernidad líquida (Bauman, 2003), donde esa liquidez viene caracterizada por lo desechable, la falta de compromiso o la baja lealtad; por el dataísmo (Harari, 2016) o por las consecuencias de instruir a la población para que se aleje de los pensamientos divergentes y se sienta cómoda en una especie de enjambre donde su identidad cobra sentido dada su homogeneidad y donde los términos contabilidad o transparencia son predominantes (Han, 2014), a nosotros, como investigadores, nos interesa conocer cuál es la percepción sobre el concepto de literatura que tiene el futuro profesorado, ya que, aunque la atmósfera audiovisual rodee sus actuaciones, el hecho literario seguirá formando parte de la cultura occidental que le trasciende, y creemos que no va a desaparecer del sistema educativo.…”
Section: Introductionunclassified